Relación del programa social juntos y el nivel de pobreza de las familias de la región de Loreto durante el periodo 2019 - Sanchez Rioja, Cicely (2022)
The conditional cash transfer (CCT) program of Peru, JUNTOS, is one of the most successful and controversial programs that the Peruvian government has to try to reduce poverty in the most vulnerable sectors of the population and guarantee a better quality of life. It began in 2005 and currently covers all the districts of Peru, specifically the entire geographical area of the department of Loreto. The objective of this work is to estimate the relationship between belonging to the JUNTOS program, the poverty level and the income level of families in the Loreto region during 2019. To shed light on the possible benefits that this social program has in the the interior of the country, specifically in the Loreto region, and can serve as a guide for future political evaluations, research and analysis on the effectiveness of social programs in the jungle region. In our results, we found a significant difference between income and the level of poverty between beneficiary and nonbeneficiary families of the program, these differences are explained by the great income inequality that the region has, and the impossibility of the social program to reduce this gap or to have a more permanent impact on reducing monetary poverty. However, the years of education show a great return on family income, proving to be a promising instrument to reduce poverty in the Loreto region.